Prediction of elastic displacement response spectra in Europe and the Middle East. - Akkar, Sinan
Empirical equations are presented for the prediction of displacement response ordinates for damping ratios of 2, 5, 10, 20 and 30% of critical and for response periods up to 4s, using 532 accelerograms from the strong-motion databank from Europe and the Middle East. The records were all re-processed and only employed for regressions at periods within the usable range, defined as a fraction of the filter cut-off and depending on the instrument type (digital or analogue), earthquake magnitude and site class. The equations can be applied to predict the geometric mean displacement and pseudo-acceleration spectra for earthquakes with moment magnitudes (M) between 5 and 7.6, and for distances up to 100km. The equations also include style-of-faulting and site class as explanatory variables. The predictions obtained from these new equations suggest that earlier European equations for spectral displacements underestimate the ordinates at longer periods as a result of severe filtering and the use of the spectral ordinates at periods too close to the filter cut-off. The results also confirm that the period defining the start of the constant displacement plateau in the Eurocode 8 (EC8) spectrum is excessively short at 2s. The results not only show that the scaling factor defined in EC8 for estimating the spectral ordinates at damping ratios different from 5% of critical are a good general approximation, but also that this scaling varies with magnitude and distance (reflecting the influence of duration) and also displays a mild dependence on response period.
Keywords: Displacement response spectra; Pseudo-acceleration spectra; Ground-motion prediction equations; European strong-motion database; Eurocode 8.; Displacement-based design; Damping ratios